Wear characteristics of patterned and un-patterned tetrahedral amorphous carbon film in the presence of synthetic and bio based lubricants. (19th December 2018) - Arslan, A; Quazi, M M; Masjuki, H H; Kalam, M A; Varman, M; Zulkifli, N W M; Jamshaid, M; Mandalan, S M; Gohar, G A; Gulzar, M; Alwi, Azham; Yarmand, Hooman; et al.
Abstract: In this article, wear performance of patterned and non-patterned tetrahedral carbon thin film (ta-C) is compared in the presence of various lubricants. For this purpose, wear tests were conducted at temperatures (40 °C–125 °C) which are normally found during automotive engine operation. Wear test were conducted at 100 N load and 120 min. The results showed that bio-based lubricant show better wear performance at 40 and 80 °C compared to PAO lubricant for both laser patterned and non-patterned ta-C thin film. However, at the temperature of 125 °C, PAO showed better wear performance than palm based TMP ester. This can be because of unstable film formation at higher temperatures in case of bio-based lubricant. It was also found that patterned ta-C thin films shows higher wear resistance than non-patterned thin film. This can be because of micro pores which can provide lubricant, capture micro and nano wear particle and behave as micro hydrodynamic bearings.